Cooperation between university and industry in the research of the suitability of agile methodologies in software development - Mattos, L. F. B. (2021)
Choosing a proper approach to manage a software development project is critical to increasing the chances to succeed in the venture. One of the great dilemmas nowadays concerns the option for an Agile or a traditional approach. There are several characteristics of software projects and the business environment in which they are carried out that must be considered while choosing the most appropriate development process. Although Agile development methodologies have been increasingly expanding and consolidating worldwide as an effective way of building software in the last two decades, they are not a one-size-fits-all approach. Knowing when to use Agile and which methodology is most suitable are the great questions that we aimed to answer in this study. In this paper, through a comprehensive revision of the Agile literature and an exploratory study, with the realization of focus group sessions with Agile practitioners and an interview with an Agile expert actively engaged in the software industry, we explored the characteristics of software development projects and organisational environments, identifying those that favour the use of an Agile approach. We also studied the main aspects that lead Agile teams to opt for one of the common Agile frameworks: Scrum, Extreme Programming (XP), Kanban, or Lean Software Development (LSD). The major goal of our study, clarifying the main aspects to be considered in the choice of an Agile methodology, is to support the decision-maker in the process of selecting an appropriate development approach.